2022
DOI: 10.3762/bjnano.13.66
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Bi2WO6/TiO2-nanotube composites derived from natural cellulose for visible-light photocatalytic treatment of pollutants

Abstract: A series of Bi2WO6/TiO2-nanotube (Bi2WO6/TiO2-NT) heterostructured composites were prepared by utilizing natural cellulose (e.g., laboratory filter paper) as the structural template. The obtained nanoarchitectonics, namely Bi2WO6/TiO2-NT nanocomposites, displayed three-dimensionally interwoven structures which replicated the initial cellulose template. The composite Bi2WO6/TiO2-NT nanotubes were formed by TiO2 nanotubes that uniformly anchored with Bi2WO6 nanoparticles of various densities on the surface. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Bi-based semiconductors, in particular, are thought to be able to surpass the limitation of the solar light-harvesting capacity of TiO 2 -based photocatalytic materials because of their smaller bandgaps. Because of its highly anisotropic Fermi surface charge, low carrier density, small electron effective mass, long electron mean free path, and extremely low band overlap energy, bismuth can transition from a semimetal to a semiconductor by shrinking its crystallite size [25,[71][72][73][74][75][76][77].…”
Section: Bismuth and Bismuth-based Nanostructured Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bi-based semiconductors, in particular, are thought to be able to surpass the limitation of the solar light-harvesting capacity of TiO 2 -based photocatalytic materials because of their smaller bandgaps. Because of its highly anisotropic Fermi surface charge, low carrier density, small electron effective mass, long electron mean free path, and extremely low band overlap energy, bismuth can transition from a semimetal to a semiconductor by shrinking its crystallite size [25,[71][72][73][74][75][76][77].…”
Section: Bismuth and Bismuth-based Nanostructured Photocatalystsmentioning
confidence: 99%
“…Bulk Bi exhibits high interband electronic transition rates that result in a negative ultraviolet-visible permittivity and a large infrared refractive index. Numerous investigations have shown that the quantum confinement effect affects the optical properties of Bi [25,[71][72][73][74][75][76][77][78][79][80]. Furthermore, nanostructured materials exhibit unique optical properties that set them apart from the corresponding bulk materials as a result of this quantum confinement.…”
Section: Structural Optoelectronic and Magnetic Propertiesmentioning
confidence: 99%